CHITOSAN COMPOSITES PREPARATION AND CHARACTERIZATION OF GUIDE TUBES FOR NERVE REPAIR - Galo Cardenas; Rodrigo Soto-Serguel (Journal of the Chilean Chemical Society, 2020)
Nerve regeneration is a biologically complex phenomenon. Once the nervous system is damaged, its recovery is difficult and causes a malfunction in other parts of the body that can occur because mature neurons do not suffer cell division. To increase the prospects of axonal regeneration and functional recovery, research has focused on the construction and design of nerve conduction channels or guide tubes. That is why a high molecular weight chitosan was used as a starting material, which was first characterized by the following analyses: moisture, ash, FTIR, TGA, total nitrogen determination, viscosity for the determination of the average molecular weight and degree of deacetylation by potentiometric titration. Once the starting chitosan is characterized, tube-shaped biomaterials are prepared based on a 4% w/v chitosan solution, using CH3COOH solvent at 1% v/v. Calcium glutamate is added to 0.5% and 1% w/v, neutralizing with NaOH 0.25N, and then taken to the molds to be frozen and subsequently freeze-dried. Finally, the materials are coated with polylactic acid, in order to achieve a strengthening in the structure of the material. These materials are also prepared in a bio clean area. The different materials are chemically and morphologically characterized by FTIR, TGA, Atomic Absorption Spectroscopy, Mechanical Properties, and Morphology and solubility test.